Lymphocyte-activation gene 3 in cancer immunotherapy: function, prognostic biomarker and therapeutic potentials - Ren, Ke; Hamdy, Hayam; Meyiah, Abdo; Elkord, Eyad (Frontiers in Immunology, 2024)
Lymphocyte-activation gene 3 (LAG-3) has emerged as a key immune checkpoint regulating immune responses in the context of cancer. The inhibitory effect of LAG-3-expressing T cells contributes to suppressing anti-tumor immunity and promoting tumor progression. This review discusses the function of LAG-3 in immune suppression, its interactions with ligands, and its potential as a prognostic biomarker for cancers. We also explore therapeutic strategies targeting LAG-3, including monoclonal antibodies, small molecule inhibitors, and CAR T cells. This review summarizes the current preclinical and clinical studies on LAG-3, highlighting the potential of therapeutic regimens targeting LAG-3 to enhance antitumor immunity and improve patients’ outcomes. Further studies are needed to fully elucidate the mechanism of action of LAG-3 and optimize its application in tumor therapy.